Kajian Strategis terhadap Hybrid Warfare dalam Konflik Rusia-Ukraina dan Implikasinya secara Global - A. Albin Dzaky Putra M. (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Hybrid Warfare strategy is a modern strategy that combines military elements and all non-military elements used by Russia against Ukraine that continues to occur. The ongoing conflict between Russia and Ukraine has implications not only regionally but also globally. This study uses a qualitative method with a literature review approach showing global implications in the field of geopolitical security, especially cyber threats for several countries. The war that occurred also had implications for food supplies and weakened global trade so that Russia received economic sanctions. The humanitarian crisis began to occur as a result of the lack of food supplies and the war that continued to claim victims including human rights violations.